Pemberdayaan Masyarakat Desa Melalui Kegiatan Workshop Usaha Mikro Kecil dan Menengah di Desa Malanuza - Bela, Maria Editha; Bhoke, Wilibaldus; Ngao, Priska; Putrini, Maria Anjelina; Goan, Bonevantura; Hari, Christina Lusiana (Abdimas Indonesian Journal, 2025)
This community service activity aims to provide real contributions to the community through various activities with the aim of improving welfare, education, health and the environment. One of the activities to improve community welfare is through UMKM workshop activities. The purpose of the UMKM workshop activity is to increase the capacity of UMKM business groups through mentoring in the management and development of UMKM businesses and to solve various problems, such as marketing problems that are not yet optimal, the availability of supporting tools that are still incomplete and the right strategy in entrepreneurship. The implementation method in this activity is field observation, problem identification, preparation of activity plans, implementation, and evaluation. The implementation of mentoring activities includes workshop activities related to UMKM development strategies, in order to provide understanding and knowledge to business groups about the steps in developing UMKM businesses. The results of this workshop activity are expected that business actors and students are able to understand the material provided and are able to apply it in entrepreneurship.